Use of Geographic Information System Technology to Evaluate Health Disparities in Smoking Cessation Class Accessibility for Patients in Louisiana Public Hospitals - Tseng, Tung Sung; Celestin, Michael D.; Yu, Qingzhao; Li, Mirandy; Luo, Ting; Moody-Thomas, Sarah (Frontiers in Public Health, 2021)
Research has shown cigarette smoking is a major risk factors for many type of cancer or cancer prognosis. Tobacco related health disparities were addressed continually in cancer screening, diagnosis, treatment, prevention and control. The present study evaluated the health disparities in attendance of smoking cessation counseling classes for 4826 patients scheduled to attend between 2005 and 2007. Of 3781 (78.4%) patients with records to calculate the distance from their home domicile to counseling sites using Geographic Information System technology, 1435 (38%) of smokers who attended counseling had shorter travel distances to counseling sites (11.6 miles, SD=11.29) compared to non-attendees (13.4 miles, SD=16.72). When the travel distance was greater than 20 miles, the estimated odds of attending decreased with greater travel distance. Smokers who actually attended were more likely to be older, female, White, living in urban areas, and receiving free healthcare. After controlling for other socio-demographic factors, shorter distances were associated with greater class attendance, and individuals more likely to attend included those that lived closer to the counseling site and in urban settings, were female, White, commercially insured, and older than their counterparts. These findings have the potential to provide important insights for reducing health disparities for cancer prevention and control, and to improve shared decision making between providers and smokers.